Biochemical analysis of α-synuclein extracted from control and Parkinson's disease colonic biopsies. (22nd February 2017) - Corbillé, Anne-Gaëlle; Preterre, Cécile; Rolli-Derkinderen, Malvyne; Coron, Emmanuel; Neunlist, Michel; Lebouvier, Thibaud; Derkinderen, Pascal
Highlights: Alpha-synuclein deposits are found in the gut in PD. Alpha-synuclein expression levels and phosphorylation status were analyzed by biochemical means in 17 PD patients. No differences in the expression levels, phosphorylation and aggregation status of alpha-synuclein was observed between controls and PD. Our study suggests that the biochemical methods tested are not adequate for the prediction of PD using gastrointestinal biopsies. Abstract: Lewy bodies and neurites, the pathological hallmarks found in the brain of Parkinson's disease (PD) patients, are primarily composed of aggregated and hyperphosphorylated alpha-synuclein. The observation that alpha-synuclein inclusions are also found in the gut of the vast majority of parkinsonian patients has led to an increasing number of studies aimed at developing diagnostic procedures based on the detection of pathological alpha-synuclein in gastrointestinal biopsies. The previous studies, which have all used immunohistochemistry for the detection of alpha-synuclein, have provided conflicting results. In the current survey, we used a different approach by analyzing the immunoreactivity pattern of alpha-synuclein separated by one- and two-dimensional electrophoresis, in colonic biopsies from PD subjects and healthy individuals. We did not observe any differences between controls and PD in the expression levels, phosphorylation or aggregation status of alpha-synuclein. Overall, our study suggests that the two biochemical methods tested here are not adequate for the prediction of PD using gastrointestinal biopsies. Further studies, using other biochemical approaches, are warranted to test whether there exists specific forms of pathological alpha-synuclein that distinguish PD from control subjects.